International Religious Freedom Act 1998 and the Issues of Religious Freedom in Muslim Countries - Mohd Lotpi, Mohd Yusob; Mohd Afandi, Salleh; Rabiatul Adawiyah, Mohd Ariffin; Abdul Majid Hafiz, Mohamad (2016)
In the late 20th centuries, the increasing international emphasis on the recognition of religious freedom had led the United States drew up the International Religious Freedom Act (1998) in October 1998. The Act aims to improve the ability of United States to advance religious freedom through its foreign affairs. However, after almost 18 years of its establishment, it is important to highlight that IRFA’s report had focused on Muslim-majority countries. In fact, many Muslim countries were classified as “Countries Particular Concern” (CPC) which equivalent to violators of religious freedom. The objective of this article is to study critically the result on the report of IRFA with particular regard to Muslim countries. The paper contends that, U.S. government had given too much attention on Muslim countries rather than other countries. We argue that, though the law has the potential to be a useful tool for United States in protecting religious freedom, the result of IRFA report in meddling affairs of Muslim-majority states is the major flaw. The paper will also examine, at glance, on the concept of religious freedom within the framework of maqasid al-shariah (the objectives of Shariah law).